Base-catalysed cleavage of lignin β-O-4 model compounds in dimethyl carbonate. Issue 11 (11th May 2015) - Dabral, Saumya; Mottweiler, Jakob; Rinesch, Torsten; Bolm, Carsten
Abstract : Dimethyl carbonate (DMC) was used as solvent and non-toxic capping agent in a base-catalysed selective cleavage of lignin model compounds. Abstract : A base-catalysed transformation and cleavage of lignin β-O-4 model compounds in dimethyl carbonate is reported. The reaction system consists of readily available bases and inexpensive dimethyl carbonate as a solvent and reagent, affording methoxy benzene or 2-aryloxyvinyl benzene derivatives in good to very good yields. The applicability of the system for the bond cleavage in an organosolv lignin sample was demonstrated.